2016
DOI: 10.1167/iovs.15-19038
|View full text |Cite
|
Sign up to set email alerts
|

Histamine-Induced Dilation of Isolated Porcine Retinal Arterioles: Role of Endothelium-Derived Hyperpolarizing Factor

Abstract: Citation: Otani S, Nagaoka T, Omae T, et al. Histamine-induced dilation of isolated porcine retinal arterioles: role of endothelium-derived hyperpolarizing factor. Invest Ophthalmol Vis Sci. 2016;57:4791-4798. DOI:10.1167/iovs.15-19038 PURPOSE. Although endothelium-dependent nitric oxide (NO)-mediated dilation of retinal arterioles has been well described, the role of endothelium-derived hyperpolarizing factor (EDHF) in the retinal arteriolar response remains unclear. In the current study, we examined the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…25,44 In contrast, we also have shown that histamine-induced dilation of porcine retinal arterioles is dependent on activation of both NOS and COX. 37 The present findings corroborate these earlier results by showing that the NOS inhibitor L-NAME attenuated the dilation of retinal arterioles from control nondiabetic pigs to histamine (Fig. 1), supporting the role of NO in this vasodilation.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…25,44 In contrast, we also have shown that histamine-induced dilation of porcine retinal arterioles is dependent on activation of both NOS and COX. 37 The present findings corroborate these earlier results by showing that the NOS inhibitor L-NAME attenuated the dilation of retinal arterioles from control nondiabetic pigs to histamine (Fig. 1), supporting the role of NO in this vasodilation.…”
Section: Discussionsupporting
confidence: 92%
“…This in vitro approach allowed us to directly assess the endothelial NOS and COX pathways. We used two endogenous vasodilator agonists, histamine 37 , 41 43 and bradykinin, 25 , 44 as pharmacologic tools to assess endothelial function of retinal arterioles. Histamine and bradykinin may exert a local impact on regulation of retinal arteriolar tone based on the existence of histamine-generating enzymes and the kallikrein-kinin system in the retinal tissue of several vertebrates including human.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the work delineating the individual contributions of SK Ca and IK Ca channels to vasodilation and tissue hyperemia was performed using mesenteric (gut) arteries as an accessible and abundant source of resistance arteries in the body [56,57,58]. However, to a lesser extent, studies also resolved clear contributions of respective K Ca channel subtypes in the microcirculation of the eye [59], brain [60,61,62], heart [63,64], lung [65,66], skeletal muscle [8,67], and kidney [68,69,70]. While it is clear that both SK Ca and IK Ca channels are integral to overall cardiovascular health (systemic vascular resistance and blood pressure control), respective K Ca contributions underlying hyperemia throughout organs may vary.…”
Section: Significance Of Skca/ikca and Trp Channels In The Blood Vmentioning
confidence: 99%